From ice to space: a greenhouse design for Moon or Mars based on a prototype deployed in Antarctica - Maiwald, Volker; Vrakking, Vincent; Zabel, Paul; Schubert, Daniel; Waclavicek, René; Dorn, Markus; Fiore, Lorenzo; Imhof, Barbara; Rousek, Tomas; Rosseti, Vittorio; Zeidler, Conrad (CEAS Space Journal, 2020)
The future of human space exploration is aimed at long-term missions to Moon and Mars. Currently, plans are elaborated by NASA, ESA, CNSA and others for a return to the lunar environment within the next decade as an intermediate step towards the goal of reaching the surface of Mars. For sustenance and crew comfort the crew of such long-duration missions should be provided with fresh food on the lunar or Martian surface. Due to the associated power demand, the required resources and technological complexity, this is a major challenge for this kind of missions. To continuously provide fresh food without the need for cargo transfer from Earth towards Moon or Mars an on-site greenhouse system is required, producing the fresh food in situ. The associated effort and cost for all resources to be transported to the base of operation prohibit any waste of resources, requiring a system operating in a (nearly) closed loop. Developing and validating a prototype for an effective and efficient greenhouse, labeled future exploration greenhouse (FEG) for space exploration has been the goal of the EDEN ISS project, funded by the EU, in the past 4 years. This paper shows the results of a design elaboration of the FEG into a greenhouse for planetary deployment on Moon or Mars. Guided by lessons learned from operating the FEG in Antarctica for one year and based on assumptions concerning the mission scenario, e.g. assuming an existing base infrastructure on-site, the presented design incorporates a plant growth area which is more than a factor of two larger than the prototype. The total mass of the cylindrical system, including equipment required during launch, transfer and landing, is about 19 mT, fitting into a Falcon 9 launcher. The versatile design is compatible with a wide variety of mission scenarios, e.g. ESA’s Moon Village, and currently public mission plans.